atp Mutants of Escherichia coli Fail To Grow on Succinate Due to a Transport Deficiency - Boogerd, Fred C. (American Society for Microbiology, 1998)
Escherichia coli atp mutants, which lack a functional H(+)-ATPase complex, are capable of growth on glucose but not on succinate or other C(4)-dicarboxylates (Suc(−) phenotype). Suc(+) revertants of an atp deletion strain were isolated which were capable of growth on succinate even though they lack the entire H(+)-ATPase complex. Complementation in trans with the yhiF gene suppressed the growth of the Suc(+) mutants on succinate, which implicates the yhiF gene product in the regulation of C(4)-dicarboxylate metabolism. Indeed, when the E. coli C(4)-dicarboxylate transporter (encoded by the dctA gene) was expressed in trans, the Suc(−) phenotype of the atp deletion strain reverted to Suc(+), which shows that the reason why the E. coli atp mutant is unable to grow aerobically on C(4)-dicarboxylates is insufficient transport capacity for these substrates.